Analisis Penerapan dan Perlakuan Akuntansi PSAK 110 Akuntansi Sukuk pada Investor Bursa Efek Indonesia - Rinaldi Rizal (Sekolah Pascasarjana Perbanas Jakarta, 2021)
This thesis is entitled Analysis of Accounting Application and Treatment of PSAK 110 Accounting for Sukuk on Indonesian Stock Exchange Investors. This research is descriptive analytical, the method used is literature review with a qualitative approach. The sample used to research is 10 (ten) major sharia banks in Indonesia that have gone public on the Indonesia Stock Exchange, which are investors who buy Sukuk, both issued by the state and private companies. The sample companies are PT BRI Syariah Tbk (BRIS), PT Bank BTPN Syariah Tbk (BTPS), PT Bank Muamalat Indonesia Tbk (BBMI), Bank Panin Dubai Syariah Tbk (PNBS), PT Bank Net Syariah Tbk (BANK), PT Bank Syariah Mandiri (BBSM), PT Bank BCA Syariah (BCAS), PT Bank Syariah Bukopin (BSBK) and PT Bank Mega Syariah (BMSY). The results of this study indicate that the application and accounting treatment of PSAK 110 Accounting for Sukuk to Indonesian Stock Exchange investors, in terms of recognition and measurement, presentation and disclosure, are in accordance with PSAK 110 Accounting for Sukuk. Keywords: Sukuk Accounting, PSAK 110, Sukuk, Investor, Syariah.